(3GbQGW GdPgH aj GdeaGNQI Hjf GdQhVI hHFQ GdYQHs - (3YHO Gddg Hf Ydj Hf GdhRjQ Gdjefj GdUfYGfjs ((3GHh Ydi GdSOj GSeGYjd Hf MSjf GdchcHGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi GfTC LfGJ eYQhTGJ hZjQ eYQhTGJ hHgPG abO CfHCfG SdWGf GdLQGcSI GdCejQ aQL bGd fHCJfi HSfOgG GdMQI eOQL s
(3BNQgG (B:s
(3eeG Qhi HQbhb YfgG haQL (B/ (3hYLd Gddge efc HGdaQL hHGdbHhd cf dfG ebGHdG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs